Effect of Drying Methods on Chemical Properties of Mango Paste (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The influence of drying methods (hot-air, microwave, and sun drying) on the bioactive compounds and mineral composition of mango paste was investigated. Mango paste samples were processed under the different drying conditions and analyzed for vitamin C, beta-carotene, lycopene, total phenolic, flavonoids content, and selected minerals, including potassium (K), iron (Fe), magnesium (Mg), calcium (Ca), and phosphorus (P). Significant differences (p < 0.05) were observed among the drying methods for all parameters evaluated.All the drying methods resulted in a reduction in vitamin C and phenolic compounds, while beta-carotene, lycopene, and most mineral elements increased significantly due to concentration effects associated with moisture removal. Fresh mango recorded the highest vitamin C content (64.08 mg/100 g), whereas hot-air drying caused the greatest reduction (25.80 mg/100 g). Sun-dried mango paste retained relatively higher vitamin C (61.62 mg/100 g) among the dried samples. Beta-carotene content increased from 5.82 mg/100 g in fresh mango to 10.92 mg/100 g in sun-dried mango paste, while lycopene content was highest in microwave-dried mango paste (2.37 mg/100 g). Total phenolic content decreased substantially after drying, with hot-air-dried mango paste recording the lowest value (0.65 mg/100 g). Conversely, microwave drying enhanced flavonoid retention, producing the highest flavonoid content (79.00 mg/100 g).Mineral analysis revealed significant increases in potassium, iron, magnesium, and calcium contents following drying. Sun-dried mango paste exhibited the highest potassium concentration (501.45 mg/100 g), whereas microwave drying produced the highest calcium content (41.55 mg/100 g). In contrast, phosphorus content decreased in all dried samples compared with fresh mango.Overall, microwave drying demonstrated superior retention of bioactive compounds and minerals, indicating its suitability for preserving the nutritional and functional quality of mango paste.